Study of the cerebellar arteries of the "macaco-prego": considerations on the nomenclature (Cebus apella, L. 1766) - Silva, Rosimeire Alves da; Ferreira, Jussara Rocha (Brazilian Journal of Veterinary Research and Animal Science, 2002)
We studied the cerebellar arteries of the "macaco-prego" (Cebus apella). Fifty-seven cerebellar hemispheres were obtained from animals used in previous investigations, so that animals were not killed for this research. The method included microdissections under light mesoscopy after injection of the arterial system with stained latex (neoprene 450 and sulvinil stain). The analysis of the samples revealed that the blood supply to the cerebellum is dependent upon the vertebral basilar system, which gave off vessels, often in pairs, to the different cerebellar regions and ventral portion of the brain stem. We identified the following arterial cerebellar trunks: caudal inferior, rostral inferior, anterior, superior and pontine. The first trunk is dependent upon the vertebral artery (100%), the second upon the basilar artery (63,15%), and the last three upon the basilar artery. The nomination of these arteries is not completely established, to our belief because of the tendency of comparing primates in general with humans, agreeing the Oficial Veterinary Nomenclature.